Preparation and Thermo-Responsive Properties of Poly(Oligo(Ethylene Glycol)Methacrylate)Copolymers with Hydroxy-Terminated Side Chain - CHEN Yangyi; SU Tong; ZHOU Shihang; XIE Chendi; LI Jingzhi; QIU Yiping (东华大学学报（英文版）, 2023)
TQ31; Thermo-responsive random copolymers,poly(2-(2-methoxyethoxy)ethoxyethyl methacrylate-co-(ethylene glycol)methyl ether methacrylate)(P(EO2-co-EO4/5))and poly(2-(2-methoxyethoxy)ethoxyethyl methacrylate-co-ethylene glycol methacrylate(P(EO2-co-EG4/5))are synthesized via atom transfer radical polymerization(ATRP).The successful synthesis and the narrow polydispersity index(PDI)of two copolymers are indicated by 1 H nuclear magnetic resonance(1 H-NMR)and gel permeation chromatography(GPC)analyses.The transition behaviors of polymers in the aqueous solution are demonstrated by changes in turbidity and particle sizes.The transition behavior of P(EO2-co-EG4/5)is found to be milder than that of P(EO2-co-EO4/5).Moreover,the presence of hydrogen bonds without thermo-responsive properties established by hydroxyl groups in the end-side chain of P(EO2-co-EG4/5)hinders the dehydration at the transition temperature(TT).Attenuated total reflection Fourier transform infrared spectrometry(ATR-FTIR)analysis along with contact angle measurements reveals that both P(EO2-co-EO4/5)and P(EO2-co-EG4/5)films undergo phase transitions from hydrophilicity to hydrophobicity above TT.By examining the swelling and collapse behaviors of the polymer films during phase transitions,it can be concluded that the end hydroxyl groups may establish hydrogen bonds with neighboring ether groups within the films,which remain intact throughout the phase transition process due to their strong bonding interactions.This leads to an increase in steric hindrance within swollen films thereby impeding dehydration processes and inducing hysteresis during phase transitions.